Teachers’ Burnout: The Role of Trait Emotional Intelligence and Social Support - Fiorilli, Caterina; Benevene, Paula; De Stasio, Simona; Buonomo, Ilaria; Romano, Luciano; Pepe, Alessandro; Addimando, Loredana (Frontiers in Psychology, 2019)
The current study investigates the relations among teachers' trait emotional intelligence, internal and external social support, and their levels of burnout. We hypothesized that both emotional intelligence and teachers' perceived social support were associated with a low level of teachers' burnout. We further expected that internal and external support mediated the relationship between trait emotional intelligence and burnout scores. Participants were 318 in-service Italian teachers. The structural equation modeling analysis supports the idea that teachers' trait emotional intelligence is strongly and directly associated with their burnout. Furthermore, internal social support (from the teachers' workplace relationships) was more effective on burnout than support forthcoming from their external context. On the contrary, the mediation hypothesis was partially supported by the empirical data. These findings shed light on the relationship between teachers' emotional competence and their burnout experience at school.